2010
DOI: 10.1071/rd10084
|View full text |Cite
|
Sign up to set email alerts
|

Effects of recipient mouse strain, sex and gonadal status on the outcome of testis tissue xenografting

Abstract: The aim of the present study was to examine factors that may affect the outcome of testis tissue xenografting. Recipient factors were examined by grafting small fragments of testis tissue from newborn piglets under the back skin of immunodeficient mice of different strains (severe combined immunodeficiency (SCID) v. nude), sex (male v. female) and gonadal status (intact v. gonadectomised) using a factorial design (eight groups; n = 7 mice per group). Recipient mice were killed after 8 months to compare the gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 28 publications
1
13
0
Order By: Relevance
“…The striking host-dependent effects were substantiated by analysis of the most advanced germ cell types showing significant differences in the degree of post-meiotic germ cell differentiation between intact male and female hosts. This observation is in agreement with a study on newborn piglet testicular tissue revealing that poor post-meiotic differentiation is observed in female hosts compared to males (25). In mice a syngeneic testicular grafting study showed efficient graft survival and good post-meiotic differentiation in female recipients (48).…”
Section: Discussionsupporting
confidence: 93%
“…The striking host-dependent effects were substantiated by analysis of the most advanced germ cell types showing significant differences in the degree of post-meiotic germ cell differentiation between intact male and female hosts. This observation is in agreement with a study on newborn piglet testicular tissue revealing that poor post-meiotic differentiation is observed in female hosts compared to males (25). In mice a syngeneic testicular grafting study showed efficient graft survival and good post-meiotic differentiation in female recipients (48).…”
Section: Discussionsupporting
confidence: 93%
“…Since earlier studies have shown no difference in survival and development of xenografts in both castrated and intact (noncastrated) mouse recipients [25,26], cryopreserved testicular tissues were xenografted onto intact nude mice. Cryopreserved rhesus monkey testes could establish spermatogenesis in intact mice [27] but not in castrated mice [28], indicating that intact mice support spermatogenesis in cryopreserved testes.…”
Section: Discussionmentioning
confidence: 99%
“…Only one recent study had systematically compared the outcome of porcine testis tissue xenografting using both strains of mice. The results showed that the percentage of recovered grafts, graft weight, seminiferous tubular density and percentage of tubules cross sections presenting germ cells was higher when SCID mice were used as hosts while no differences were found in the percentage of tubules with elongated or round spermatids (Abbasi & Honaramooz 2010). It could be interesting to analyze whether these results are maintained when using another species as donor for the testicular tissue.…”
Section: Factors Affecting the Outcome Of Testis Tissue Xenograftingmentioning
confidence: 99%
“…2012) but did not accelerate germ cell differentiation in bull or pig testis grafts (Huang et al . 2008, Abbasi & Honaramooz 2010). …”
Section: Factors Affecting the Outcome Of Testis Tissue Xenograftingmentioning
confidence: 99%
See 1 more Smart Citation